Handbook of Basel III capital : enhancing bank capital in practice - Ramirez, Juan. (West Sussex, UK : Wiley, 2017)
The Handbook delves deep into the principles underpinning the capital dimension of Basel III to provide a more advanced understanding of real-world implementation. Going beyond the simple overview or model, this book merges theory with practice to help practitioners work more effectively within the regulatory framework, and utilise the complex rules to more effectively allocate and enhance capital. A European perspective covers the CRD IV directive and associated guidance, but practitioners across all jurisdictions will find value in the strategic approach to decisions surrounding business lines and assets; an emphasis on analysis urges banks to shed unattractive positions and channel capital toward opportunities that actually fit their risk and return profile. Real-world cases demonstrate successful capital initiatives as models for implementation, and in-depth guidance on Basel III rules equips practitioners to more effectively utilise this complex regulatory treatment. The specifics of Basel III implementation vary, but the underlying principles are effective around the world. This book expands upon existing guidance to provide a deeper working knowledge of Basel III utility, and the insight to use it effectively. The Handbook of Basel III Capital - Enhancing Bank Capital in Practice provides advanced guidance for advanced practitioners, and real-world implementation insight.
Includes index.
Includes bibliographical references p. 531.
ne 17/08/2022
Loans
Keywords: Bank capital; Banks and banking, International; International finance; Business and economics--Finance.